Neoextractivism and Class Formation: Lessons from the Orinoco Mining Arc Project in Venezuela. (January 2019) - Angosto-Ferrández, Luis Fernando
The Arco Minero del Orinoco (Orinoco Mining Arc—AMO) project, launched in 2016, demonstrates that Bolivarian governments have been unsuccessful in overcoming extractivism and rentier capitalism as structuring foundations of the Venezuelan state and its politics, but it simultaneously confirms that these governments remain supported by a bloc made up of heterogeneous class fractions primarily amalgamated around a demand for socioeconomic development. Mining extractivism is the focus of a rapid readjustment of regional and national class formation. The implementation of the Orinoco Mining Arc project could reactivate government-led redistribution in the short-to-medium term, reversing the deterioration of living conditions of the popular classes and potentially reactivating participation of some of their members in small and medium-sized economic ventures. However, given the political conditions under which the project was launched, the main immediate beneficiaries (to different degrees) are capital holders, corporatist groups within the state apparatus, and sectors of the indigenous population directly involved in extractivism. El proyecto Arco Minero del Orinoco (Orinoco Mining Arc—AMO), lanzado en 2016, demuestra que los gobiernos bolivarianos han fracasado en superar el extractivismo y el capitalismo rentista como fundamentos estructurales del Estado venezolano y su política, pero simultáneamente confirma que estos gobiernos permanecen apoyado por un bloque formado por fracciones de clase heterogéneas principalmente aglutinadas en torno a una demanda de desarrollo socioeconómico. El extractivismo minero es el foco de un rápido reajuste de la formación de clases regionales y nacionales. La implementación del proyecto Orinoco Mining Arc podría reactivar la redistribución liderada por el gobierno en el corto a mediano plazo, revirtiendo el deterioro de las condiciones de vida de las clases populares y potencialmente reactivando la participación de algunos de sus miembros en pequeñas y medianas empresas económicas. Sin embargo, dadas las condiciones políticas bajo las cuales se lanzó el proyecto, los principales beneficiarios inmediatos (en diferentes grados) son los titulares de capital, los grupos corporatistas dentro del aparato estatal y los sectores de la población indígena directamente involucrados en el extractivismo.